2017
DOI: 10.1002/tox.22513
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidic acid induces apoptosis through the p38 MAPK signaling pathway in human hepatocellular carcinoma

Abstract: Cantharidin analogs exhibit anticancer activities, including apoptosis. However, the molecular mechanisms underlying the effects of cantharidic acid (CA), a cantharidin analog, on apoptosis in hepatocellular carcinoma (HCC) cells are unclear. Thus, in this study, we evaluated the anticancer activities of CA by investigating its ability to trigger apoptosis in SK-Hep-1 cells. Our data demonstrated that CA effectively inhibited the proliferation of SK-Hep-1 cells in a dose-dependent manner. Furthermore, CA effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Additionally, our results match a previous study which reported that, Bax deletion, an apoptotic protein, in a hepatocyte‐specific BCL‐xL knockout model, suppressed hepatocarcinogenesis . However, our results are in contrast with previous studies showing that activation of the ASK1‐p38 MAPK signalling cascade induces apoptosis in many HCC cell lines . Additionally, Bao et al reported that p38 MAPK induces apoptosis in HepG2 and Huh7 cells through upregulation of apoptosis‐related proteins, including p53, caspases and Bcl‐2 proteins …”
Section: Discussionsupporting
confidence: 84%
“…Additionally, our results match a previous study which reported that, Bax deletion, an apoptotic protein, in a hepatocyte‐specific BCL‐xL knockout model, suppressed hepatocarcinogenesis . However, our results are in contrast with previous studies showing that activation of the ASK1‐p38 MAPK signalling cascade induces apoptosis in many HCC cell lines . Additionally, Bao et al reported that p38 MAPK induces apoptosis in HepG2 and Huh7 cells through upregulation of apoptosis‐related proteins, including p53, caspases and Bcl‐2 proteins …”
Section: Discussionsupporting
confidence: 84%
“…CAC was reported to inhibit growth of oral squamous cell carcinoma (OSCC) and testicular germ cell tumor respectively through endoplasmic reticulum (ER) stress and unfolded protein response (UPR) induction and ERK‐mediated caspase‐3 activation . Moreover, Feng et al reports that CAC induces apoptosis in SK‐Hep‐1 cells through a p38‐mediated apoptotic pathway …”
Section: Introductionmentioning
confidence: 99%
“…Seol et al's [ 30 ] results suggest that Riluzole, an amyotrophic lateral sclerosis (ALS) drug, has an anticancer effect on HCC. Feng et al [ 31 ] reported that cantharidic acid inhibits HCC cell proliferation by inducing cell apoptosis through the p38 MAPK signaling pathway. Nwosu et al [ 32 ] reported that downregulated genes (HCC versus non-HCC) were enriched in the PPAR signaling pathway based on each of the 8 HCC datasets downloaded from the Gene Expression Omnibus (GEO).…”
Section: Discussionmentioning
confidence: 99%